A filter coated with ultra-low anti-reflection film and its process
By plating an ultra-low anti-reflection film composed of silicon sol, aluminum sol, carboxylated carbon nanotubes and uniform dispersant on the filter, the problem of unsatisfactory anti-reflection effect of the existing filter and easy dust accumulation is solved, and high light transmittance and self-cleaning function are achieved.
Patent Information
- Application Number
- CN202411247016.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing filters with ultra-low-reflection films have poor anti-reflection effect, and are prone to dust accumulation, affecting light transmittance.
The ultra-low anti-reflection film is formed by using a combination of silica sol, aluminum sol, carboxylated carbon nanotubes and uniform dispersant.
It realizes the ultra-low reflection effect of the filter surface, improves the light transmission performance and imaging quality, and also has self-cleaning function, reducing the frequency of daily maintenance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optical elements, and in particular to an optical filter coated with an ultra-low anti-reflection film and a process thereof. Background Art
[0002] Filters are optical devices used to select the desired radiation band. One common feature of filters is that no filter can make the image of celestial objects brighter, because all filters absorb certain wavelengths, making objects darker.
[0003] With the continuous development of science and technology, filters are used more and more widely in optical systems, and their performance directly affects the imaging quality and visual effects of optical systems. However, traditional filters are used in optical systems to control the light passing through a specific wavelength, but these filters usually have a high reflectivity, resulting in light energy loss and image quality degradation. In order to reduce the reflection loss of light, a method of coating an anti-reflection film is usually adopted, but the anti-reflection effect of the anti-reflection film in the prior art is not ideal, and the current filters are prone to dust accumulation, which will also have an adverse effect on the light transmittance of the filter. Therefore, the development of a filter coated with an ultra-low anti-reflection film and its process is of great significance to improving the performance of the filter. Summary of the invention
[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a filter coated with an ultra-low anti-reflection film and a process thereof, which solves the problem that the anti-reflection film on the existing filter coated with an ultra-low anti-reflection film has an unsatisfactory anti-reflection effect and is prone to dust accumulation, which in turn has an adverse effect on the light transmittance of the filter.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A filter coated with an ultra-low anti-reflection film, comprising an optical filter and an ultra-low anti-reflection film on the surface of the optical filter;
[0007] Wherein, the ultra-low anti-reflection film comprises the following components in parts by weight:
[0008] 70-80 parts of silica sol, 50-55 parts of aluminum sol, 0.8-2.2 parts of carboxylated carbon nanotubes and 0.05-0.17 parts of a uniform dispersant;
[0009] Wherein, the uniform dispersant is prepared by the following steps:
[0010] Step s1: add carbazole, 3,5-bis(trifluoromethyl)iodobenzene, cuprous iodide, potassium phosphate and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 0.5-1h at a temperature of 25-30°C and a stirring rate of 400-500r / min, then raise the temperature to 150-160°C and continue stirring and reacting for 20-25h. After the reaction is completed, cool the reaction product to room temperature, pour it into distilled water, extract it with dichloromethane 2-3 times, combine the extracts and dry them with anhydrous sodium sulfate, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate 1;
[0011] Step s2: Add intermediate 1, N-bromosuccinimide and N,N-dimethylformamide to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, and stir the reaction for 20-25 hours at a temperature of 25-30°C and a stirring rate of 400-500r / min. After the reaction is completed, cool the reaction product to room temperature, pour it into distilled water, and then extract it with dichloromethane 2-3 times. Combine the extracts and dry the extracts with anhydrous sodium sulfate, then vacuum filter, rotary evaporate the filtrate to remove the solvent, then elute with a mixed solvent, collect the eluate, and then rotary evaporate the eluate to remove the solvent to obtain intermediate 2;
[0012] Step s3: Add intermediate 2, eugenol, anhydrous potassium carbonate and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 400-500r / min, then raise the temperature to reflux and continue stirring the reaction for 8-10 hours. After the reaction is completed, cool the reaction product to room temperature, pour it into distilled water, and then extract it with dichloromethane for 2-3 times. Combine the extracts and dry the extracts with anhydrous sodium sulfate, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate 3;
[0013] Step s4: Add intermediate 3, mercaptopropyltrimethoxysilane, 1,8-diazacyclo[5,4,0]undec-7-ene and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 30-50 minutes at a temperature of 25-30°C and a stirring rate of 400-500r / min, then continue to stir and react for 20-30 minutes at a temperature of 50-55°C, then continue to stir and react for 20-30 minutes at a temperature of 100-110°C, then continue to stir and react for 20-30 minutes at a temperature of 150-155°C, and after the reaction, cool the reaction product to room temperature, then rotary evaporate to remove the solvent to obtain a uniform dispersant.
[0014] As a further embodiment of the present invention: the usage ratio of the carbazole, 3,5-bis(trifluoromethyl)iodobenzene, cuprous iodide, potassium phosphate and N,N-dimethylformamide in step s1 is 10 mmol:12-15 mmol:10-12 mmol:10-12 mmol:50-60 mL.
[0015] As a further scheme of the present invention: the usage ratio of the intermediate 1, N-bromosuccinimide and N,N-dimethylformamide in step s2 is 10mmol:25-30mmol:70-80mL; the mixed solvent is a mixture of petroleum ether and dichloromethane in a volume ratio of 5:1.
[0016] As a further scheme of the present invention: the usage ratio of the intermediate 2, eugenol, anhydrous potassium carbonate and N,N-dimethylformamide in step s3 is 10 mmol: 11-13 mmol: 13-15 mmol: 80-100 mL.
[0017] As a further scheme of the present invention: the usage ratio of the intermediate 3, mercaptopropyltrimethoxysilane, 1,8-diazacyclo[5,4,0]undec-7-ene and N,N-dimethylformamide in step s4 is 10 mmol:22-25 mmol:0.2-0.3 mmol:100-120 mL.
[0018] As a further solution of the present invention: the silica sol is prepared by the following steps:
[0019] Add anhydrous ethanol and ammonia water into a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, add tetraethoxysilane dropwise while stirring at a temperature of 50-55°C and a stirring rate of 400-500r / min, and control the dropping rate to 1-2 drops / s. After the addition is completed, continue stirring and reacting for 6-7h to obtain silica sol.
[0020] As a further solution of the present invention: the usage ratio of the anhydrous ethanol, ammonia water and tetraethoxysilane is 60-65 mL: 12-22 mL: 6.5-6.9 mL; the mass fraction of the ammonia water is 25-27%.
[0021] As a further solution of the present invention: the aluminum sol is prepared by the following steps:
[0022] Aluminum nitrate, ethanolamine and ethylene glycol isopropyl ether are added into a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction for 3-3.5 hours at a temperature of 25-30° C. and a stirring rate of 400-500 r / min to obtain aluminum sol.
[0023] As a further solution of the present invention: the usage ratio of the aluminum nitrate, ethanolamine and ethylene glycol isopropyl ether is 9.2-9.6 g: 1.5-1.7 mL: 50-55 mL.
[0024] As a further solution of the present invention: the carboxylated carbon nanotubes are prepared by the following steps:
[0025] Add carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 2-3 hours at a temperature of 25-30°C and a stirring rate of 400-500r / min, then continue to stir and react for 20-30 minutes under reflux conditions, then continue to stir and react for 5-6 hours under a temperature of 100-110°C, after the reaction is completed, pour the reaction product into distilled water, then vacuum filter, place the filter cake in a vacuum drying oven, and dry it at a temperature of 65-70°C for 2-3 hours to obtain carboxylated carbon nanotubes.
[0026] As a further solution of the present invention: the usage ratio of the carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid is 3g:30-35mL:10-12mL; the outer diameter of the carbon nanotubes is 5-15nm, and the length is 0.5-2μm; the mass fraction of the concentrated sulfuric acid is 98.3%, and the mass fraction of the concentrated nitric acid is 68%.
[0027] As a further solution of the present invention: a process for coating an optical filter with an ultra-low anti-reflection film comprises the following steps:
[0028] Step 1: Weigh 70-80 parts of silica sol, 50-55 parts of aluminum sol, 0.8-2.2 parts of carboxylated carbon nanotubes and 0.05-0.17 parts of a uniform dispersant according to weight, and set aside;
[0029] Step 2: Mix silica sol, aluminum sol, carboxylated carbon nanotubes and a uniform dispersant, and then ultrasonically disperse them for 1-2 hours under an ultrasonic power of 200-300 W to obtain an ultra-low anti-reflection immersion solution;
[0030] Step 3: After cleaning the filter, immerse it in the ultra-low anti-reflection immersion liquid, then pull it vertically upward at a rate of 5-7mm / s to form a film, then place it in a vacuum drying oven, dry it at a temperature of 30-35℃ for 1-1.5h, then heat it to 150-160℃ and dry it for 30-40min to obtain a filter coated with an ultra-low anti-reflection film.
[0031] Beneficial effects of the present invention:
[0032] The present invention discloses an optical filter coated with an ultra-low anti-reflection film and a process thereof. The steps are as follows: silica sol, aluminum sol, carboxylated carbon nanotubes and a uniform dispersant are mixed, and then ultrasonically dispersed to obtain an ultra-low anti-reflection impregnation liquid. The optical filter is cleaned and then immersed in the ultra-low anti-reflection impregnation liquid, and then vertically pulled upward to form a film, and then dried to obtain the optical filter coated with an ultra-low anti-reflection film. In the process, silica sol, aluminum sol and carboxylated carbon nanotubes are used as main raw materials, and the three are reasonably compounded, and modified with a uniform dispersant, and finally an ultra-low anti-reflection impregnation liquid is used to form an ultra-low anti-reflection film on the surface of the optical filter. The optical filter coated with an ultra-low anti-reflection film and a process thereof can achieve an ultra-low reflection effect on the surface of the optical filter, effectively improving the light transmittance and imaging quality of the optical filter. At the same time, the process of the present invention is simple, low-cost and has broad application prospects. The refractive index of SiO2 formed with silica sol as the silicon source is low, and it has chemical It has the advantages of high stability and corrosion resistance, and is currently the most widely used anti-reflection coating material. Carbon nanotubes are considered to be an excellent light absorber, which has a strong suppression effect on incident light, further improving its anti-reflection effect. Aluminum oxide also has a certain anti-reflection enhancement effect, while increasing the wear resistance of the ultra-low anti-reflection film and increasing the surface roughness, providing conditions for the super-hydrophobicity of the ultra-low anti-reflection film, and forming micro-nodules and micro-pits on the surface, forming multiple scattering, and indirectly reducing the occurrence of reflection. After treatment with a uniform dispersant, the silica sol, aluminum sol, and carboxylated carbon nanotubes can be evenly dispersed, so that the three are evenly distributed, and the ultra-low anti-reflection film formed has uniform performance everywhere, and it is given low surface energy, so that it has excellent hydrophobicity, avoiding dust accumulation, and dust accumulation will also have an adverse effect on the light transmittance of the filter, and the self-cleaning of the filter can be achieved, thereby greatly reducing the frequency of daily maintenance of the filter.
[0033] In the process of preparing the filter coated with ultra-low anti-reflection film, a uniform dispersant is first prepared, and carbazole and 3,5-bis(trifluoromethyl)iodobenzene are first reacted, and the iodine atom on 3,5-bis(trifluoromethyl)iodobenzene reacts with the secondary amino group on carbazole, thereby introducing a large number of CF bonds into carbazole to obtain intermediate 1, and then intermediate 1 is reacted with N-bromosuccinimide, and N-bromosuccinimide bromines intermediate 1, and a bromine atom is introduced into the para position of the C atom connected to the carbazole N atom of intermediate 1 to obtain intermediate 2, and then intermediate 2 is reacted with eugenol, and the bromine atom on intermediate 2 reacts with the hydroxyl group on eugenol. Reaction, introduction of alkenyl, to obtain intermediate 3, then the intermediate 3, mercaptopropyltrimethoxysilane reaction, the alkenyl on the intermediate 3 and the mercapto on the mercaptopropyltrimethoxysilane click reaction, to obtain a uniform dispersant; the molecular structure of the uniform dispersant contains a large number of siloxane groups, which can be hydrolyzed to form silanols, and grafted onto the particle surfaces of silica sol, aluminum sol, and carboxylated carbon nanotubes, which can greatly improve their dispersibility, and can connect the three in the form of chemical bonds to improve the binding force of the three, and the molecular structure of the uniform dispersant contains a large number of CF bonds, which reduces the surface energy of the particle surface, giving it excellent hydrophobicity. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] This embodiment is a process for coating an ultra-low anti-reflection film on an optical filter, comprising the following steps:
[0037] Step S1: 60 mL of anhydrous ethanol and 12 mL of 25% ammonia water were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and 6.5 mL of tetraethoxysilane was added dropwise while stirring at a temperature of 50° C. and a stirring rate of 400 r / min. The dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the stirring reaction was continued for 6 hours to obtain a silica sol;
[0038] Step S2: 9.2 g of aluminum nitrate, 1.5 mL of ethanolamine and 50 mL of ethylene glycol isopropyl ether were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 3 h to obtain aluminum sol;
[0039] Step S3: 3 g of carbon nanotubes, 30 mL of concentrated sulfuric acid with a mass fraction of 98.3%, and 10 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, and stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 2 h, and then continued to stir and react for 20 min under the condition of heating and reflux, and then continued to stir and react for 5 h under the condition of heating at 100° C. After the reaction is completed, the reaction product is poured into distilled water, and then vacuum filtered, and the filter cake is placed in a vacuum drying oven and dried at a temperature of 65° C. for 2 h to obtain carboxylated carbon nanotubes;
[0040] Step S4: 10 mmol of carbazole, 12 mmol of 3,5-bis(trifluoromethyl)iodobenzene, 10 mmol of cuprous iodide, 10 mmol of potassium phosphate and 50 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at 25° C. and a stirring rate of 400 r / min for 0.5 h, and then the mixture was heated to 150° C. and continued to stir for 20 h. After the reaction was completed, the reaction product was cooled to room temperature, and then poured into distilled water, and then extracted twice with dichloromethane, the extracts were combined and dried over anhydrous sodium sulfate, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate 1;
[0041] Step S5: 10 mmol of intermediate 1, 25 mmol of N-bromosuccinimide and 70 mL of N, N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The reaction was stirred for 20 hours at a temperature of 25° C. and a stirring rate of 400 r / min. After the reaction was completed, the reaction product was cooled to room temperature, poured into distilled water, and then extracted twice with dichloromethane. The extracts were combined and dried over anhydrous sodium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent, and then eluted with a mixed solvent of petroleum ether and dichloromethane in a volume ratio of 5:1, and the eluate was collected. The eluate was then rotary evaporated to remove the solvent to obtain intermediate 2;
[0042] Step S6: 10 mmol of intermediate 2, 11 mmol of eugenol, 13 mmol of anhydrous potassium carbonate and 80 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 25° C. and a stirring rate of 400 r / min for 20 min, and then the mixture was heated to reflux and continued to stir for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, poured into distilled water, and then extracted twice with dichloromethane. The extracts were combined and dried over anhydrous sodium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain intermediate 3;
[0043] Step S7: 10 mmol of intermediate 3, 22 mmol of mercaptopropyltrimethoxysilane, 0.2 mmol of 1,8-diazacyclo[5,4,0]undec-7-ene and 100 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was stirred for reaction at a temperature of 50° C. for 20 min, and then the mixture was stirred for reaction at a temperature of 100° C. for 20 min, and then the mixture was stirred for reaction at a temperature of 150° C. for 20 min. After the reaction, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a uniform dispersant;
[0044] Step S8: weigh 70 parts of silica sol, 50 parts of aluminum sol, 0.8 parts of carboxylated carbon nanotubes and 0.05 parts of a uniform dispersant according to weight and set aside;
[0045] Step S9: mixing silica sol, aluminum sol, carboxylated carbon nanotubes and a uniform dispersant, and then ultrasonically dispersing for 1 hour under an ultrasonic power of 200 W to obtain an ultra-low anti-reflection immersion solution;
[0046] Step S10: After cleaning the filter, immerse it in an ultra-low anti-reflection immersion liquid, then pull it vertically upward at a rate of 5 mm / s to form a film, then place it in a vacuum drying oven, dry it at a temperature of 30°C for 1 hour, and then heat it to 150°C and dry it for 30 minutes to obtain a filter coated with an ultra-low anti-reflection film.
[0047] Embodiment 2:
[0048] This embodiment is a process for coating an ultra-low anti-reflection film on an optical filter, comprising the following steps:
[0049] Step S1: 62 mL of anhydrous ethanol and 17 mL of 26% ammonia water were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and 6.7 mL of tetraethoxysilane was added dropwise while stirring at a temperature of 52° C. and a stirring rate of 450 r / min. The dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the stirring reaction was continued for 6.5 h to obtain a silica sol;
[0050] Step S2: 9.4 g of aluminum nitrate, 1.6 mL of ethanolamine and 52 mL of ethylene glycol isopropyl ether were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 28° C. and a stirring rate of 450 r / min for 3.2 h to obtain an aluminum sol;
[0051] Step S3: 3 g of carbon nanotubes, 32 mL of concentrated sulfuric acid with a mass fraction of 98.3%, and 11 mL of concentrated nitric acid with a mass fraction of 68% were added to a three-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, and stirred for reaction at a temperature of 28° C. and a stirring rate of 450 r / min for 2.5 h, and then continued to stir and react for 25 min under the condition of heating and reflux, and then continued to stir and react for 5.5 h under the condition of heating to 105° C. After the reaction, the reaction product was poured into distilled water, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 68° C. for 2.5 h to obtain carboxylated carbon nanotubes;
[0052] Step S4: 10 mmol of carbazole, 13 mmol of 3,5-bis(trifluoromethyl)iodobenzene, 11 mmol of cuprous iodide, 11 mmol of potassium phosphate and 55 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The reaction was stirred for 0.8 h at a temperature of 28° C. and a stirring rate of 450 r / min, and then the temperature was raised to 155° C. and the stirring reaction was continued for 22 h. After the reaction was completed, the reaction product was cooled to room temperature, and then poured into distilled water, and then extracted twice with dichloromethane, the extracts were combined and dried over anhydrous sodium sulfate, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate 1;
[0053] Step S5: 10 mmol of intermediate 1, 28 mmol of N-bromosuccinimide and 75 mL of N, N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The reaction was stirred for 22 hours at a temperature of 28° C. and a stirring rate of 450 r / min. After the reaction was completed, the reaction product was cooled to room temperature, poured into distilled water, and then extracted with dichloromethane for 3 times. The extracts were combined and dried over anhydrous sodium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent, and then eluted with a mixed solvent of petroleum ether and dichloromethane in a volume ratio of 5:1, and the eluate was collected. The eluate was then rotary evaporated to remove the solvent to obtain intermediate 2;
[0054] Step S6: 10 mmol of intermediate 2, 12 mmol of eugenol, 14 mmol of anhydrous potassium carbonate and 90 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 28° C. and a stirring rate of 450 r / min for 25 min, and then the mixture was heated to reflux and continued to stir for 9 h. After the reaction, the reaction product was cooled to room temperature, poured into distilled water, and extracted twice with dichloromethane. The extracts were combined and dried over anhydrous sodium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain intermediate 3;
[0055] Step S7: 10 mmol of intermediate 3, 23 mmol of mercaptopropyltrimethoxysilane, 0.25 mmol of 1,8-diazacyclo[5,4,0]undec-7-ene and 110 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 450 r / min for 40 min, and then the mixture was heated to 52° C. and continued to stir for reaction for 25 min, and then the mixture was heated to 105° C. and continued to stir for reaction for 25 min, and then the mixture was heated to 152° C. and continued to stir for reaction for 25 min. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a uniform dispersant;
[0056] Step S8: weigh 75 parts of silica sol, 52 parts of aluminum sol, 1.5 parts of carboxylated carbon nanotubes and 0.11 parts of a uniform dispersant according to weight, and set aside;
[0057] Step S9: mixing silica sol, aluminum sol, carboxylated carbon nanotubes and a uniform dispersant, and then ultrasonically dispersing for 1.5 hours at an ultrasonic power of 250 W to obtain an ultra-low anti-reflection immersion solution;
[0058] Step S10: After cleaning the filter, immerse it in an ultra-low anti-reflection immersion liquid, then pull it vertically upward at a rate of 6 mm / s to form a film, then place it in a vacuum drying oven, dry it at a temperature of 32°C for 1.2 hours, then heat it to 155°C and dry it for 35 minutes to obtain a filter coated with an ultra-low anti-reflection film.
[0059] Embodiment 3:
[0060] This embodiment is a process for coating an ultra-low anti-reflection film on an optical filter, comprising the following steps:
[0061] Step S1: 65 mL of anhydrous ethanol and 22 mL of 27% ammonia water were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and 6.9 mL of tetraethoxysilane was added dropwise while stirring at a temperature of 55° C. and a stirring rate of 500 r / min. The dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the stirring reaction was continued for 7 hours to obtain a silica sol;
[0062] Step S2: 9.6 g of aluminum nitrate, 1.7 mL of ethanolamine and 55 mL of ethylene glycol isopropyl ether were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 3.5 h to obtain aluminum sol;
[0063] Step S3: 3 g of carbon nanotubes, 35 mL of concentrated sulfuric acid with a mass fraction of 98.3%, and 12 mL of concentrated nitric acid with a mass fraction of 68% were added to a three-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 3 h, and then continued to stir and react for 30 min under the condition of heating and reflux, and then continued to stir and react for 6 h under the condition of heating to 110° C. After the reaction, the reaction product was poured into distilled water, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 70° C. for 3 h to obtain carboxylated carbon nanotubes;
[0064] Step S4: 10 mmol of carbazole, 15 mmol of 3,5-bis(trifluoromethyl)iodobenzene, 12 mmol of cuprous iodide, 12 mmol of potassium phosphate and 60 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at 30° C. and a stirring rate of 500 r / min for 1 h, and then the mixture was heated to 160° C. and the stirring reaction was continued for 25 h. After the reaction was completed, the reaction product was cooled to room temperature, and then poured into distilled water, and then extracted with dichloromethane for 3 times. The extracts were combined and dried over anhydrous sodium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain intermediate 1;
[0065] Step S5: 10 mmol of intermediate 1, 30 mmol of N-bromosuccinimide and 80 mL of N, N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The reaction was stirred for 25 hours at a temperature of 30° C. and a stirring rate of 500 r / min. After the reaction was completed, the reaction product was cooled to room temperature, poured into distilled water, and then extracted with dichloromethane for 3 times. The extracts were combined and dried over anhydrous sodium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent, and then eluted with a mixed solvent of petroleum ether and dichloromethane in a volume ratio of 5:1, and the eluate was collected. The eluate was then rotary evaporated to remove the solvent to obtain intermediate 2;
[0066] Step S6: 10 mmol of intermediate 2, 13 mmol of eugenol, 15 mmol of anhydrous potassium carbonate and 100 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 30° C. and a stirring rate of 500 r / min for 30 min, and then the mixture was heated to reflux and continued to stir for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, poured into distilled water, and then extracted with dichloromethane for 3 times. The extracts were combined and dried over anhydrous sodium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain intermediate 3;
[0067] Step S7: 10 mmol of intermediate 3, 25 mmol of mercaptopropyltrimethoxysilane, 0.3 mmol of 1,8-diazacyclo[5,4,0]undec-7-ene and 120 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 50 min, and then the mixture was heated to 55° C. and continued to stir for reaction for 30 min, and then the mixture was heated to 110° C. and continued to stir for reaction for 30 min, and then the mixture was heated to 155° C. and continued to stir for reaction for 30 min. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a uniform dispersant;
[0068] Step S8: 80 parts of silica sol, 55 parts of aluminum sol, 2.2 parts of carboxylated carbon nanotubes and 0.17 parts of a uniform dispersant were weighed and set aside;
[0069] Step S9: mixing silica sol, aluminum sol, carboxylated carbon nanotubes and a uniform dispersant, and then ultrasonically dispersing for 2 hours under an ultrasonic power of 300 W to obtain an ultra-low anti-reflection immersion solution;
[0070] Step S10: After cleaning the filter, immerse it in an ultra-low anti-reflection immersion liquid, then pull it vertically upward at a rate of 7 mm / s to form a film, then place it in a vacuum drying oven, dry it at a temperature of 35°C for 1.5 hours, then heat it to 160°C and dry it for 40 minutes to obtain a filter coated with an ultra-low anti-reflection film.
[0071] Comparative Example 1:
[0072] This comparative example is a process for coating an ultra-low anti-reflection film on a filter, comprising the following steps:
[0073] Step S1: 65 mL of anhydrous ethanol and 22 mL of 27% ammonia water were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and 6.9 mL of tetraethoxysilane was added dropwise while stirring at a temperature of 55° C. and a stirring rate of 500 r / min. The dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the stirring reaction was continued for 7 hours to obtain a silica sol;
[0074] Step S2: Weigh 80 parts of silica sol and 0.17 parts of a uniform dispersant according to weight and set aside;
[0075] Step S3: mixing the silica sol and the uniform dispersant, and then ultrasonically dispersing them for 2 hours under the condition of an ultrasonic power of 300 W to obtain an ultra-low anti-reflection immersion liquid;
[0076] Step S4: After cleaning the filter, immerse it in an ultra-low anti-reflection immersion liquid, then pull it vertically upward at a rate of 7 mm / s to form a film, then place it in a vacuum drying oven, dry it at a temperature of 35°C for 1.5 hours, then heat it to 160°C and dry it for 40 minutes to obtain a filter coated with an ultra-low anti-reflection film.
[0077] Comparative Example 2:
[0078] This comparative example is a process for coating an ultra-low anti-reflection film on a filter, comprising the following steps:
[0079] Step S1: 9.6 g of aluminum nitrate, 1.7 mL of ethanolamine and 55 mL of ethylene glycol isopropyl ether were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 3.5 h to obtain aluminum sol;
[0080] Step S2: weigh 55 parts of aluminum sol and 0.17 parts of a uniform dispersant according to weight, and set aside;
[0081] Step S3: mixing the aluminum sol and the uniform dispersant, and then ultrasonically dispersing for 2 hours under the condition of an ultrasonic power of 300 W to obtain an ultra-low anti-reflection immersion liquid;
[0082] Step S4: After cleaning the filter, immerse it in an ultra-low anti-reflection immersion liquid, then pull it vertically upward at a rate of 7 mm / s to form a film, then place it in a vacuum drying oven, dry it at a temperature of 35°C for 1.5 hours, then heat it to 160°C and dry it for 40 minutes to obtain a filter coated with an ultra-low anti-reflection film.
[0083] Comparative Example 3:
[0084] This comparative example is a process for coating an ultra-low anti-reflection film on a filter, comprising the following steps:
[0085] Step S1: 3 g of carbon nanotubes, 35 mL of concentrated sulfuric acid with a mass fraction of 98.3%, and 12 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 3 h, and then continued to stir and react for 30 min under the condition of heating and reflux, and then continued to stir and react for 6 h under the condition of heating to 110° C. After the reaction is completed, the reaction product is poured into distilled water, and then vacuum filtered, and the filter cake is placed in a vacuum drying oven and dried at a temperature of 70° C. for 3 h to obtain carboxylated carbon nanotubes;
[0086] Step S2: weigh 2.2 parts of carboxylated carbon nanotubes and 0.17 parts of a uniform dispersant according to weight, and set aside;
[0087] Step S3: mixing the carboxylated carbon nanotubes and the uniform dispersant, and then ultrasonically dispersing them for 2 hours under the condition of an ultrasonic power of 300 W to obtain an ultra-low anti-reflection immersion solution;
[0088] Step S4: After cleaning the filter, immerse it in an ultra-low anti-reflection immersion liquid, then pull it vertically upward at a rate of 7 mm / s to form a film, then place it in a vacuum drying oven, dry it at a temperature of 35°C for 1.5 hours, then heat it to 160°C and dry it for 40 minutes to obtain a filter coated with an ultra-low anti-reflection film.
[0089] Comparative Example 4:
[0090] This comparative example is a process for coating an ultra-low anti-reflection film on a filter, comprising the following steps:
[0091] Step S1: 65 mL of anhydrous ethanol and 22 mL of 27% ammonia water were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and 6.9 mL of tetraethoxysilane was added dropwise while stirring at a temperature of 55° C. and a stirring rate of 500 r / min. The dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the stirring reaction was continued for 7 hours to obtain a silica sol;
[0092] Step S2: 9.6 g of aluminum nitrate, 1.7 mL of ethanolamine and 55 mL of ethylene glycol isopropyl ether were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 3.5 h to obtain aluminum sol;
[0093] Step S3: 3 g of carbon nanotubes, 35 mL of concentrated sulfuric acid with a mass fraction of 98.3%, and 12 mL of concentrated nitric acid with a mass fraction of 68% were added to a three-necked flask equipped with a stirrer, a thermometer, and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 3 h, and then continued to stir and react for 30 min under the condition of heating and reflux, and then continued to stir and react for 6 h under the condition of heating to 110° C. After the reaction, the reaction product was poured into distilled water, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 70° C. for 3 h to obtain carboxylated carbon nanotubes;
[0094] Step S4: 80 parts of silica sol, 55 parts of aluminum sol, 2.2 parts of carboxylated carbon nanotubes and 0.17 parts of mercaptopropyltrimethoxysilane were weighed and set aside;
[0095] Step S5: mixing silica sol, aluminum sol, carboxylated carbon nanotubes and mercaptopropyltrimethoxysilane, and then ultrasonically dispersing them for 2 hours under an ultrasonic power of 300 W to obtain an ultra-low anti-reflection immersion solution;
[0096] Step S6: After cleaning the filter, immerse it in an ultra-low anti-reflection immersion liquid, then pull it vertically upward at a rate of 7 mm / s to form a film, then place it in a vacuum drying oven, dry it at a temperature of 35°C for 1.5 hours, then heat it to 160°C and dry it for 40 minutes to obtain a filter coated with an ultra-low anti-reflection film.
[0097] The performance of the filter coated with ultra-low anti-reflection film of Examples 1-3 and Comparative Examples 1-4 is specifically as follows: the transmittance and reflectivity of the coating in the visible light (400-800nm) range are measured using a EU-2600R ultraviolet-visible spectrophotometer, and the water contact angle is measured using a German KRUSS standard DSA25 contact angle meter. The test results are as follows: Referring to the data in the above table, according to the comparison between Examples 1-3 and Comparative Examples 1-4, it can be known that after the reasonable compounding of silica sol, aluminum sol and carboxylated carbon nanotubes and the modification treatment with a uniform dispersant, the filter coated with an ultra-low anti-reflection film has excellent light transmittance and anti-reflection effect, and high hydrophobicity, so that it has a good self-cleaning effect.
[0098] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0099] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A filter coated with an ultra-low anti-reflection film, characterized in that: Including filters and ultra-low anti-reflection coatings on the filter surfaces; Wherein, the ultra-low anti-reflection film comprises the following components in parts by weight: 70-80 parts of silica sol, 50-55 parts of aluminum sol, 0.8-2.2 parts of carboxylated carbon nanotubes and 0.05-0.17 parts of a uniform dispersant; Wherein, the silica sol is prepared by the following steps: Anhydrous ethanol and ammonia water are added to a three-necked flask, and then tetraethoxysilane is added dropwise while stirring. After the addition is completed, stirring is continued to react to obtain silica sol; the usage ratio of anhydrous ethanol, ammonia water and tetraethoxysilane is 60-65mL:12-22mL:6.5-6.9mL; the mass fraction of ammonia water is 25-27%; Wherein, the aluminum sol is prepared by the following steps: Aluminum nitrate, ethanolamine and ethylene glycol isopropyl ether are stirred for reaction to obtain aluminum sol; the dosage ratio of the aluminum nitrate, ethanolamine and ethylene glycol isopropyl ether is 9.2-9.6 g: 1.5-1.7 mL: 50-55 mL; Wherein, the carboxylated carbon nanotubes are prepared by the following steps: The carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid are stirred for reaction, and after the reaction is completed, the reaction product is poured into distilled water, and then vacuum filtered, and the filter cake is dried to obtain carboxylated carbon nanotubes; the amount ratio of the carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid is 3g:30-35mL:10-12mL; the outer diameter of the carbon nanotubes is 5-15nm, the length is 0.5-2μm, the mass fraction of the concentrated sulfuric acid is 98.3%, and the mass fraction of the concentrated nitric acid is 68%; Wherein, the uniform dispersant is prepared by the following steps: Step s1: stirring carbazole, 3,5-bis(trifluoromethyl)iodobenzene, cuprous iodide, potassium phosphate and N,N-dimethylformamide for reaction, cooling the reaction product after the reaction, then pouring it into distilled water, extracting and drying the extract, then vacuum filtering, and rotary evaporating the filtrate to obtain intermediate 1; Step s2: stirring the intermediate 1, N-bromosuccinimide and N,N-dimethylformamide for reaction, cooling the reaction product after the reaction, and then pouring it into distilled water, extracting and drying the extract, vacuum filtering, rotary evaporating the filtrate, eluting, and rotary evaporating the eluate to obtain the intermediate 2; Step s3: stirring the intermediate 2, eugenol, anhydrous potassium carbonate and N,N-dimethylformamide for reaction, cooling the reaction product after the reaction, and then pouring it into distilled water, extracting and drying the extract, and then vacuum filtering and rotary evaporating the filtrate to obtain the intermediate 3; Step s4: stirring the intermediate 3, mercaptopropyltrimethoxysilane, 1,8-diazacyclo[5,4,0]undec-7-ene and N,N-dimethylformamide to react, cooling the reaction product after the reaction, and then rotary evaporating to obtain a uniform dispersant.
2. The optical filter coated with an ultra-low anti-reflection film according to claim 1, characterized in that: The usage ratio of the carbazole, 3,5-bis(trifluoromethyl)iodobenzene, cuprous iodide, potassium phosphate and N,N-dimethylformamide in step s1 is 10 mmol:12-15 mmol:10-12 mmol:10-12 mmol:50-60 mL.
3. The optical filter coated with an ultra-low anti-reflection film according to claim 1, characterized in that: The usage ratio of the intermediate 1, N-bromosuccinimide and N,N-dimethylformamide in step s2 is 10 mmol: 25-30 mmol: 70-80 mL.
4. The optical filter coated with an ultra-low anti-reflection film according to claim 1, characterized in that: The usage ratio of the intermediate 2, eugenol, anhydrous potassium carbonate and N,N-dimethylformamide in step s3 is 10 mmol: 11-13 mmol: 13-15 mmol: 80-100 mL.
5. The optical filter coated with an ultra-low anti-reflection film according to claim 1, characterized in that: The usage ratio of the intermediate 3, mercaptopropyltrimethoxysilane, 1,8-diazacyclo[5,4,0]undec-7-ene and N,N-dimethylformamide in step s4 is 10 mmol:22-25 mmol:0.2-0.3 mmol:100-120 mL.
6. A process for coating an ultra-low anti-reflection film on an optical filter as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Weigh 70-80 parts of silica sol, 50-55 parts of aluminum sol, 0.8-2.2 parts of carboxylated carbon nanotubes and 0.05-0.17 parts of a uniform dispersant according to weight, and set aside; Step 2: Mix silica sol, aluminum sol, carboxylated carbon nanotubes and a uniform dispersant, and then ultrasonically disperse them for 1-2 hours under an ultrasonic power of 200-300 W to obtain an ultra-low anti-reflection immersion solution; Step 3: After cleaning the filter, immerse it in the ultra-low anti-reflection immersion liquid, then pull it vertically upward at a rate of 5-7mm / s to form a film, then place it in a vacuum drying oven, dry it at a temperature of 30-35℃ for 1-1.5h, then heat it to 150-160℃ and dry it for 30-40min to obtain a filter coated with an ultra-low anti-reflection film.
Citation Information
Patent Citations
Coating composition for antireflection and antireflection film prepared by using the same
CN101573639A
Filter optical coating machine with feeding mechanism and coating method of filter optical coating machine
CN117604456A